The right to the city in informal settlements:: two case studies of post-disaster adaptation in Latin America - Lopez Barrera, Silvina; Thompson, Diego (ARCC Conference Repository, 2019)
Today small-towns in western Uruguay are facing challenges related to informal settlements development, intensification of industrial agriculture, and climate change. In the last decade, different strategic plans and policies carried out by governments at multiple levels have attempted to regularize and/or resettle informal settlements in different towns and cities. Despite governmental efforts, informal settlements continue to grow in areas that are at high environmental risk, and where social-spatial fragmentation has increased between the formal and informal fabric. Lefebvre's concept "right to the city” is a response to social-spatial inequalities and it emphasizes the idea that disenfranchised communities have the right to occupy and transform urban space. Using Lefebvre's "right to the city” and "the production of space”, this paper studies informal housing and informal settlements in two neighborhoods in a small-town in western Uruguay and how they adapt to climate change consequences. It reveals how local residents occupy and transform space in two informal neighborhoods to solve their housing needs and to access to resources and infrastructure after an extreme weather event. Based on two case studies, this article reveals spatial patterns of informal settlements, the relationship between formal and informal fabric, and the ways post-disaster informal settlements and environments are represented. Field- work was conducted in 2018 and methods included spatial mapping analysis, semi-structured interviews with key actors, participant observation, and analyses of secondary data. Findings suggest that top-down bureaucratic decision-making process during post-disaster reconstruction limited residents' agency and their right to participate and transform the urbanization process and the places they inhabit. This decision-making process was guided by restricted representations of space determining whether or not residents would qualify for subsidized housing programs. This study aims to encourage communities to develop community-based initiatives that could allow them not only to anticipate and react to environmental stresses but to thrive in the long-term future.